Perlunya Konsep Kimia Secara Benar Pada Buku Ajar Kimia SMA - Sri Winarni (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
Text book of chemistry is one of the most common learning sources that used at SMA. In reality, there is still some text book of chemistry at SMA which imprecise the explanation. This is one matter that causes students’ misconception in chemistry concept. For that, it is a need of chemistry text book that gives right explanation towards chemistry concept.